Grant's atlas of anatomy - Agur, A. M. R. 4 0 16; (John Charles Boileau), 1886-1973. Lee, Ming J.;Grant, J. C. Boileau; 5 (Philadelphia : Lippincott Williams & Wilkins, 1999)
Presents color illustrations based on actual dissections of the human body; features schematic drawings that clarify anatomical concepts; and includes diagnostic images, muscle tables, legends and clinical comments, and other study tools.
Includes bibliographical references and index.
Booklist
Professional.
Keywords: 2 -- 0; 6; atlases. -- Human anatomy;Human anatomy;Anatomy, Regional;Human anatomy -- Atlases.;Atlases.;Atlases.; 20; 2